Perspectives for low energy reactions measurements at the new LEMA beam-line. (December 2020) - Acosta, L; Chávez, E; Barrón-Palos, L; Andrade, E; Marín-Lámbarri, DJ; Miranda, J; Ortiz, ME; Favela, F; Huerta, A
Abstract: Towards the end of 2017, a new beam line was commissioned at the Laboratorio Nacional de Espectrometría de Masas con Aceleradores (LEMA) at Instituto de Física of the Universidad Nacional Autónoma de México (IFUNAM). Initially, LEMA was a 1 MV tandetron accelerator just dedicated to Accelerator Mass Spectrometry (AMS); nowadays, the new line adopted the main characteristics of the AMS system in a natural way: i.e., it has a high precision measurement of the beam energy and a very high and stable current (tens of μ A) depending of charge state of each isotope. The precise low energy limit around 400 keV opens a window to study reactions in the region of interest for Astrophysics. At the same time, the LEMA beam-line allows to develop experiments combining nuclear reactions with AMS, as well the developing of all of kind of Ion Beam Analysis (IBA) studies. In this work the main characteristics of the line, the ancillary systems and the perspectives for low energy measurements for nuclear studies and applications are described.